(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Ivan Mykhailovych Logai, Dr Sc (Med), Professor, a recipient of the State Prize of Ukraine, Honored Worker of Science and Technology of Ukraine, Director of the Filatov Institute from 1985 to 2003, a distinguished scientist, ophthalmologist, teacher and public figure, passed away on March 17, 2020.